2018
DOI: 10.1002/jcp.26469
|View full text |Cite
|
Sign up to set email alerts
|

Effect of miR‐182 on hepatic fibrosis induced by Schistosomiasis japonica by targeting FOXO1 through PI3K/AKT signaling pathway

Abstract: The study aimed to investigate the impact of miR-182 and FOXO1 on S. japonica-induced hepatic fibrosis. Microarray analysis was performed to screen out differential expressed miRNAs and mRNAs. Rat hepatic fibrosis model and human hepatocellular cell line LX-2 were used to study the effect of miR-182 and FOXO1. qRT-PCR and Western blot were used to detect the expression of miR-182, FOXO1 or other fibrosis markers. The targeting relationship between FOXO1 and miR-182 was verified by luciferase reporter assay. Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 36 publications
(42 reference statements)
0
19
0
Order By: Relevance
“…13,45 In the present study, miR-182 expression was found to be significantly higher in the HIV mono-infected group, which has already been studied as a noninvasive biomarker for a number of infectious diseases. [28][29][30][31] One of these studies showed that upon Schistosoma mansoni infection, the IL-4 cytokine upregulates miR-182 expression Th2-Treg cells, thereby suppressing IL-2 secretion of the Th1 response. 30 Another found the IL-4 cytokine in significantly higher levels in HIV mono-infected subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13,45 In the present study, miR-182 expression was found to be significantly higher in the HIV mono-infected group, which has already been studied as a noninvasive biomarker for a number of infectious diseases. [28][29][30][31] One of these studies showed that upon Schistosoma mansoni infection, the IL-4 cytokine upregulates miR-182 expression Th2-Treg cells, thereby suppressing IL-2 secretion of the Th1 response. 30 Another found the IL-4 cytokine in significantly higher levels in HIV mono-infected subjects.…”
Section: Discussionmentioning
confidence: 99%
“…miR‐182 has thus been described as a noninvasive biomarker for a number of infectious diseases, such as HIV, HCV, sepsis and schistosomiasis . In the specific case of leishmaniasis, miR‐210 upregulation plays a role in apoptotic signalling pathway and miR‐122 downregulation is related to VL pathogenesis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Moreover, other possible miRNAs related to IPF are also under study. miR-182-5p was found to have significant upregulated expression in hepatic fibrosis [15][16][17] and peritoneal fibrosis. 18 Huang et al found that overexpressed miR-182 can regulate FOXO1 negatively and prompt the development of hepatic fibrosis.…”
Section: Introductionmentioning
confidence: 98%
“…18 Huang et al found that overexpressed miR-182 can regulate FOXO1 negatively and prompt the development of hepatic fibrosis. 15 Liu et al found that miR-182 might play an important role in the process of peritoneal fibrosis. 18 However, the potential effect of miR-182-5p on pulmonary fibrosis has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%